Prevalence of thoracic pain in patients with chronic obstructive pulmonary disease and relationship with patient characteristics: a cross-sectional observational study. Issue 1 (December 2016) - Janssen, D.; Wouters, E.; Parra, Y.; Stakenborg, K.; Franssen, F.
Abstract Background Objectives of this study were to evaluate the prevalence of thoracic pain in patients with chronic obstructive pulmonary disease (COPD) and its relationship with Forced Expiratory Volume in the first second (FEV1 ), static hyperinflation, dyspnoea, functional exercise capacity, disease-specific health status, anxiety, and depression. Methods This cross-sectional observational study included patients with COPD entering pulmonary rehabilitation. Participants underwent spirometry, plethysmography, and measurement of single breath diffusion capacity. Pain was assessed using a multidimensional, structured pain interview. In addition, dyspnoea severity (Modified Medical Research Council Dyspnoea Scale (mMRC)), functional exercise capacity (six-minute walking distance (6MWD)), disease-specific health status (COPD Assessment Test (CAT)), and symptoms of anxiety and depression (Hospital Anxiety Depression Scale (HADS)) were recorded. Results 55 of the included 67 participants reported chronic pain (82.1 %). 53.7 % had thoracic pain. After considering multiple comparisons, only younger age and worse CAT scores were related with the presence of thoracic pain (p  = 0.01). There were no relationships between thoracic pain and FEV1, static lung hyperinflation, diffusion capacity, mMRC score, 6MWD, anxiety or depression. Conclusion Thoracic pain is highly prevalent in COPD patients and is related to impaired disease-specific health status, but there is no relationship with FEV1, static hyperinflation, dyspnoea severity or functional exercise capacity.